A rare case of digital artery aneurysm. (June 2019) - Vinnicombe, Zak; Little, Max; Nicola, Alexi; Ibañez, Javier
Abstract: True aneurysms of the arteries of the hand are vanishingly rare. We report a case detailing the surgical management of a 44-year old gentleman with a true common digital artery aneurysm. This report adds to the current sparse literature on digital artery aneurysms and their presentation, investigation and management.